Hanan Al-Shaykh, Emily Nasrallah, and Ghada Al-Samman’s perceptions of masculinity crisis - Ithawi, Sally Abdulateef Dheyab (Research Journal in Advanced Humanities, 2025)
The present study tackles the crisis of masculinity as depicted in several Arabic novels written by prominent female authors, including Hanan Al-Shaykh, Emily Nasrallah, and Ghada Al-Samman. It highlights that the masculinity crisis is not limited to men alone, but is closely and profoundly connected to women, their position in society, and the way they are perceived. Since masculinity and femininity are deeply intertwined, the crisis of masculinity can be understood through the dynamics of the man-woman relationship. Accordingly, the present study builds upon the central premise that there is a causal link between the crisis of masculinity and violence against women in all its forms and dimensions. It explores how this crisis serves as a primary contributor to the challenges and issues women face.The study examines the crisis of masculinity from two main perspectives. The first perspective is related to its relation to the issue of honor, which places the burden of upholding it on women. The second perspective is related to the obsession with controlling and illuminating women as a reflection of masculine insecurity within the socio-cultural Arab context.